2021
DOI: 10.1016/j.jaad.2020.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Association of breast and colorectal cancer in patients with central centrifugal cicatricial alopecia: A retrospective, cross-sectional pilot study

Abstract: Funding sources: None. Conflicts of interest: None disclosed. IRB approval status: Reviewed and approved by the University of Pennsylvania IRB (834059).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A 4.68× increase in the odds of having uterine leiomyomas compared with race-, age-, and sex-matched controls was also observed in a retrospective study at Johns Hopkins Hospital (p < 0.001) [24]. Additionally, Brown et al demonstrated that in patients with biopsy-proven CCCA (159 of 742), 4.4% had a history of breast cancer compared with the 4079 controls (1.8%) (odds ratio 2.49; 95% confidence interval 1.06-4.92; p = 0.02) [25]. Both latter conditions are associated with an abnormal proliferation of fibrous tissue and once again demonstrate a crossover of the pathogenesis to different organ systems.…”
Section: Clinical Associationsmentioning
confidence: 72%
See 2 more Smart Citations
“…A 4.68× increase in the odds of having uterine leiomyomas compared with race-, age-, and sex-matched controls was also observed in a retrospective study at Johns Hopkins Hospital (p < 0.001) [24]. Additionally, Brown et al demonstrated that in patients with biopsy-proven CCCA (159 of 742), 4.4% had a history of breast cancer compared with the 4079 controls (1.8%) (odds ratio 2.49; 95% confidence interval 1.06-4.92; p = 0.02) [25]. Both latter conditions are associated with an abnormal proliferation of fibrous tissue and once again demonstrate a crossover of the pathogenesis to different organ systems.…”
Section: Clinical Associationsmentioning
confidence: 72%
“…Both latter conditions are associated with an abnormal proliferation of fibrous tissue and once again demonstrate a crossover of the pathogenesis to different organ systems. The average age of diagnosis of breast cancer was 62.9 years [25]. While the types of breast cancer were not delineated in the study, an association between dysregulated PADI3, upregulated MMP9, triple-negative inflammatory breast cancer (TNIBC), and triple-negative non-inflammatory breast cancer (TN-NIBC) has been documented in the literature [5,6,23].…”
Section: Clinical Associationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Brown-Korsah et al 19 looked at the risk of colorectal and breast cancers in patients with CCCA. All Black women 18 years or older with a biopsy-proven diagnosis of CCCA were included in the retrospective chart review.…”
Section: Resultsmentioning
confidence: 99%